Screening legume green manures as nitrogen sources to succeeding non-legume crops - Carsky, R.; Reid, W.S.; Suhet, A.R.; Lathwell, D.J. (1990)
A buried bag incubation technique was proposed to monitor N release from soil and decomposing green manure. The technique would facilitate not only the screening of legumes as sources of N but also measurement of the N supplying capacity of soils. Several tropical legumes were incorporated into field plots followed either by maize (Zea mays L.) or by bare fallow. Soil samples from the plow layer containing the incorporated green manure were placed in low density polyethylene bags and buried within the plow layer under the maize crop for in situ incubation. Periodic withdrawal of the bags was accompanied by fallow soil profile sampling. Above ground N accumulation by maize was equally well correlated to N release measured by either method although the bag technique required much less labor. Supplemental experiments suggested that N accumulation in the bags was reduced due to inadequate O2 diffusion but only when O2 demand was high and soil water potential was high. The results show that in situ bag incubation alone or together with fallow soil sampling can be used to estimate the N supplying potential of soil and leguminous residues.